The variability of wind-driven currents in the Norwegian Trench - Enge, Anna; Pietrzak, Julie D.; van Prooijen, Bram C. (Frontiers in Marine Science, 2025)
The Norwegian Trench (NT) is the main pathway for North Sea water into the Atlantic Ocean and for Atlantic Water (AW) into the North Sea. The processes that determine the cross-shelf exchange through the NT are key to understanding the variability of the salt budgets in the North Sea. Here, high-resolution numerical simulations from Copernicus Marine Services (CMEMS) for two recent years (2022, 2023) reveal new sources of variability of the flows in the NT. We find that wind regulates the flows in the NT, particularly in enabling the outflow of the fresh-water river plume, the Norwegian Coastal Current (NCC), in the Skagerrak during easterly wind conditions. Strong NCC outflows are associated with transport in a northward direction into the Atlantic Ocean. Furthermore, intensified eddy activity at the surface is found during strong NCC flows, causing high velocity surface currents sometimes exceeding magnitudes of 1 m/s. AW inflows partly compensate the northward outflows, keeping the net transport of 2–3 Sv constant over both years. However, the magnitudes of the AW inflows are small compared to the NCC. AW inflows that are comparable to the NCC outflows only occur during northerly winds in winter. We show that the variability of surface flows in the NT is wind induced, but that the effects of the canyon-like shape of the NT and seasonality of winds and river discharges introduce more variable deep flows than previously considered.